Missed Abortion - Triana Puti Nendes; Teuku Yudhi Iqbal (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Missed abortion is a condition where the fetus dies before the 20th week, but remains in the uterus for several weeks after the fetus dies. The cause of missed abortion is still not known with certainty, but it is thought to be due to the influence of the hormone progesterone. This case report was carried out against Mrs. E is 34 years old in Bebesen Village, Central Aceh in 2022. The diagnosis is made based on anamnesis, physical examination and supporting examination in the form of ultrasound. After the diagnosis is confirmed, the patient undergoes operative treatment in the form of curettage.